PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR NEGERI 020 PADANG MUTUNG - Rahman '; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the fact that the learning outcomes of students in science subjects low it can be seen from the symptoms is of 20 students, 12 people or 61% of students do not reach KKM set is 65. As many as 12 people or 63% of students no homework the teacher. When given exercises 13 people or 66% of students do with cheating, of 10 test questions only 5 to 6 questions answered correctly. The purpose of this research is to improve learning outcomes fifth grade science students of Sekolah Dasar Negeri 020 Padang Mutung by implementing cooperative learning model type group investigation. This research is a classroom action research conducted in Class IV 020 SD Negeri Padang Mutung Kampar District Kampar District, Riau Province. Research instruments consisted of a Learning Tool used in this research is guided by the Education Unit Level Curriculum (SBC), known as Curriculum 2006 learning device consists of a syllabus, lesson plans, student worksheets and observation sheet. Based on data analysis of student activity first meeting sikuls I average student activity 54% with the classification of